Case report: Characterization of a rare pathogenic variant associated with loss of COL3A1 expression in vascular Ehlers Danlos syndrome - Manhas, Janvie; Lohani, Lov Raj; Seethy, Ashikh; Kumar, Uma; Gamanagatti, Shivanand; Sen, Sudip (Frontiers in Cardiovascular Medicine, 2022)
The vascular subtype of Ehlers Danlos Syndrome (vEDS) is a rare connective tissue disorder characterised by spontaneous arterial, bowel or organ rupture. The diagnosis of vEDS is established in a proband by identification of a heterozygous pathogenic variant in the alpha-1 gene of type III collagen(COL3A1) by molecular analysis. In this report, we present a case of vEDS with life threatening, spontaneous arterial dissections in association with an uncharacterized rare variant of COL3A1, exon19:c.1340G>A. Primary culture of patient skin fibroblasts followed by immunofluorescence revealed a complete absence of COL3A1 protein expression as well as altered morphology. Electron microscopy of the cultured fibroblasts showed abnormal vacuoles in the cytoplasm suggestive of a secretory defect. In this study, we have performed functional characterization of the COL3A1 exon19:c.1340G>A variant for the first time and this may now be classified as likely pathogenic in vEDS.